Пошаговое объяснение:
5 целых 4/27-1 целых 8/9=5 целых 4/27- 1 целая 24/27=4 целых 31/27- 1 целая 24/27=3 целых 7/27
х=3 целых 7/27
сначала смешанные переводим в неправильные получается
139/27-х=17/9
приводим к общему знаменателю
139/27-х=51/27
х=139/27-51/27
х=88/27=3 целых 7/27
Пошаговое объяснение:
5 целых 4/27-1 целых 8/9=5 целых 4/27- 1 целая 24/27=4 целых 31/27- 1 целая 24/27=3 целых 7/27
х=3 целых 7/27
Пошаговое объяснение:
сначала смешанные переводим в неправильные получается
139/27-х=17/9
приводим к общему знаменателю
139/27-х=51/27
х=139/27-51/27
х=88/27=3 целых 7/27